2019
DOI: 10.3390/ijerph16142605
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Compounds and Willingness to Buy for Reduced-Additives Salami. An Outlook on Italian Consumers

Abstract: The consumption pattern of salami has been subjected to relatively widespread attention by academician, but few studies concerning the health implications of salami consumption have been published. Since additives and product origins represent important attributes for salami, the objective of this paper is twofold: (i) to explore the role of two additives, salt and nitrates, in addition to the Italian origin, in relation to consumer attitudes and preferences towards salami, (ii) to segment consumer behaviour b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
1
14
1
Order By: Relevance
“…The preference of consumers for chouriço without nitrite or nitrate might be related to the more characteristic aromatization of those including wine or wine plus garlic but may also be due to the fact that they recognize these products as "less industrial" or more similar to homemade products, which are recognized as healthier due to the absence of food additives, as was observed from analyzing comments during the FGs and the trends found with the CATA and hedonic evaluations. Some groups of consumers have a serious concern about the healthiness of foods with chemical additives, and they are willing to pay more for "green-label" foods [62,63]. Although in the present work, the use of additives was not revealed to consumers, the appearance of the products, namely their bright red color, was suggestive of the use of additives, which might have impaired the appreciation for such products.…”
Section: Sensory Implications Of Different Chouriço Formulationscontrasting
confidence: 52%
“…The preference of consumers for chouriço without nitrite or nitrate might be related to the more characteristic aromatization of those including wine or wine plus garlic but may also be due to the fact that they recognize these products as "less industrial" or more similar to homemade products, which are recognized as healthier due to the absence of food additives, as was observed from analyzing comments during the FGs and the trends found with the CATA and hedonic evaluations. Some groups of consumers have a serious concern about the healthiness of foods with chemical additives, and they are willing to pay more for "green-label" foods [62,63]. Although in the present work, the use of additives was not revealed to consumers, the appearance of the products, namely their bright red color, was suggestive of the use of additives, which might have impaired the appreciation for such products.…”
Section: Sensory Implications Of Different Chouriço Formulationscontrasting
confidence: 52%
“…Secondly, in accordance with Di Vita et al (2019a), two non-parametric test were used to determine if there were statistically significant differences between the mean value of preferences expressed by gender (with a Mann-Whitney U Test) and to test the differences between items of Section 'Materials and methods' of the questionnaire (tested with a Kruskal-Wallis H Test).…”
Section: Discussionmentioning
confidence: 99%
“…If the initial hypothesis is rejected, it means that the attributes are not related to each other in the sample (Verbeke and Viaene 1999). This methodology is widely accepted in various sectors (human resources management, psychology, market research) and is used to make critical decisions for the future (Di Vita et al 2019a). PCA has also been widely used to describe consumer behaviour or product characteristics in the agri-food sector (Pourov a and Stehlik 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These included the price, base meat product, and healthy ingredients. Di Vita et al [ 53 ] emphasized that the price is one of the most important factors in determining the quality level of the salami investigated. Besides, the authors concluded that certain socio-economic segments of consumers show a significant willingness to pay extra for low salt content and nitrate-free salami.…”
Section: Literature Reviewmentioning
confidence: 99%